Down regulation of prothrombinase by activated protein C during prothrombin activation - Y. Kim, Paul; E. Nesheim, Michael (Thrombosis and Haemostasis, 2010)
Activated protein C (aPC) proteolytically inactivates factor Va (FVa) and thereby downregulates prothrombinase. Although FVa inactivation by aPC has been studied extensively, the inactivation of prothrombinase during prothrombin activation has not. Therefore, prothrombin activation initiated both without and with aPC (5.0, 7.5 or 10.0 nM) was monitored over time by fluorescence. The experiments were performed with 0.075 nM FVa and 1.0 nM FXa, and with these concentrations reversed. The time courses of the residual prothrombinase activity with aPC, determined from the slopes of fluorescence over time, were pseudo first order with both limiting and excess FVa. With FVa limiting or in excess, the second rate constants for inactivation of prothrombinase were 1.98 ± 0.09 x 105 M-1s-1 and 2.54 ± 0.13 x 105 M-1s-1 , respectively. The former value is 101-fold smaller than that for FVa inactivation by aPC alone. Since with limiting FVa the second order rate constants for prothrombinsase inactivation and FVa inactivation are equal, FVa is protected 101-fold, presumably by both FXa and prothrombin. In contrast, with excess FVa, the calculated rate constant for FVa inactivation exceeds that for prothrombinase inactivation 17.3-fold, which reflects a loss of protection by FXa. Since the protective effects of the two proteins are theoretically multiplicative, FXa protected 17.3-fold and prothrombin protected 5.8-fold. With 150 nM protein S and limiting FVa, prothrombinase inactivation was two-fold faster, yet it was still protected 91-fold. These studies show that FVa is down-regulated by aPC during prothrombin activation, but both FXa and prothrombin protect FVa in a multiplicative way, with or without protein S.
Keywords: Coagulation factors; protein C/S pathway; regulation